Pemanfaatan Pupuk Hayati terhadap Pertumbuhan, Hasil Padi dan Sifat Kimia Tanah pada Lahan Sawah Irigasi - Ridha Nurlaily; Agus Supriyo (Jurnal Riset Agribisnis dan Peternakan, 2020)
Industrial waste, both in liquid and solid form, often causes environmental pollution, either in the form of an unpleasant odor or a dark color. One of the industrial waste that makes alcohol is processed and added with multi-strain microbes to become Biological Fertilizer (Ciunik). The purpose of this study was to study the use of Ciunik's biological fertilizers on the growth and yield of irrigated rice fields, to obtain information about the effect of Ciunik fertilizer on the chemical properties of rice fields. The research was carried out on irrigated rice fields in Batang Experimental Garden (KP) Batang Regency from March to August 2016. Randomized block design (RAK) with 4 repetitions of 6 fertilization treatments consisting of fertilization according to farmer/comparison (P0), NPK fertilization based on tools Rice Field Soil Test / PUTS (P1), Fertilization Recommendation from the Ministry of Agriculture no. 44 of 2007 (P2), Fertilization 25% Recommendation PUTS + Ciunik (P3), Fertilization 50% Recommendation PUTS + Ciunik (P4), Fertilization 75% Recommendation PUTS + Ciunik (P5). Analysis of growth and yield data used analysis of variance. If there were differences between treatments, it was continued with Duncan's Difference Test (UBD), 05. Soil microbial population data was carried out by descriptive analysis. The results showed that the application of Ciunik biological fertilizer 3 times per application, namely 5 lt / ha (at 0-3 Hbt, 15 Hst, and 25-30 Hst) combined with 75% of the NPK recommended by PUTS (P5) increased. Rice yields were 26.9% (7,450 t Gkg / ha) above control (5,219 t Gkg / ha), but not different from rice yields that applied the recommended fertilizer PUTS (P1) and MOA No. 40 th 2007 (P2). The application of Ciunik's liquid biological fertilizer to rice plants did not affect some of the chemical properties of the paddy soil.